Dampak Sekolah Ramah Anak Terhadap Pencegahan Bullying dan Kekerasan di SMPIT Al Mumtaz Jayanti Tangerang - Mumu Zainal Mutaqin; Dirga Ayu Lestari; Sanusi Sanusi; M Muslim; Siti Humaeroh; Solihin Solihin (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2025)
This study aims to analyze and describe in depth the program, implementation, and impact of SRA as a strategy for preventing bullying and violence in schools. The main focus is to identify the extent to which SRA policies, character building, and community involvement contribute to creating an inclusive and non-aggressive school culture. This study uses a qualitative descriptive method. Data were collected through in-depth interviews with the principal and vice principal for curriculum, who served as key informants in the implementation of SRA. Supporting data were obtained from indirect observation and review of documents related to school policy. The results of this discussion explain that the child-friendly school program at SMPIT Al Mumtaz Jayanti Tangerang is implemented holistically through two main pillars: a clear anti-violence policy and the integration of character values such as empathy, tolerance, and discipline into the curriculum. This implementation includes training teachers to effectively handle bullying and using learning methods that encourage cooperation among students. The direct impact of the SRA program is evident in the significant decrease in the number of bullying cases, the increase in students' courage to report incidents, and the creation of a safe and conducive school environment. Meanwhile, the indirect impact is a comprehensive transformation of the school climate to be more inclusive, fostering solidarity, and increasing social responsibility, which ultimately contributes to the sustainable prevention of violence and the formation of positive character in students.